Food and Nutritional Insecurity of Bolsa Família Program Beneficiaries - Motozo, Vanessa Patrícia Pereira; Ribeiro, Luciana Cisoto; Oliveira, Rinaldo Eduardo Machado de; Goulart, Juliana Letícia Pereira; Franco, Laercio Joel (O Mundo da Saúde, 2023)
This study aims to evaluate the food and nutritional insecurity of families benefiting from the Bolsa Família Program residing in the western health district of the city of Ribeirão Preto, São Paulo. This is a cross-sectional study of a population subset carried out from January to October 2018 through interviews with 246 participants of the Bolsa Família Program. Socioeconomic and demographic variables and food and nutritional insecurity data were collected using the Brazilian Food Insecurity Scale. Food and nutritional insecurity were at 94.3%, of which 27.6% had a moderate level, and 25.6% had a severe level. There was a predominance of female heads of households (97.6%), mixed-race ethnicity (54.9%), a low education level (53.3%), and unemployed individuals (64.6%). The highest frequency of beneficiary families belonged to the intermediate social stratum (54%), resided in their own homes (62.6%), and had children under seven years old (57.7%). Regarding the families, 60.4% had received the benefit for more than 48 months, 74.3% received an amount of R$ 200.00 or less, and 70.7% used most of the funds to purchase food. The study highlighted a high vulnerability among the families, indicating a situation of food deprivation and/or hunger experienced by the families.